Prevalence of titanium hypersensitivity in patients with titanium implants: A systematic review and meta-analysis - Rajsandeep Singh; Gurvanit Lehl; Arshad Bin Hussain; Tejal Nivrutti Abhang; Manisha Mangesh Kulkarni; Mohamed Fadul A Elagib; Rahul V C Tiwari (Wolters Kluwer Medknow Publications, 2021)
Background: With increase in exposure to titanium in daily life and its use in medical procedures, there is a greater chance for developing titanium hypersensitivity. Our aim and objective is to examine whether patient patients with titanium implants had a greater incidence of titanium hypersensitivity or not. Titanium is widely considered to have good biocompatibility. A passivating surface layer of TiO2 is formed when exposed to air which gives it good corrosion resistance. These properties along with its high strength, lightweight, and improvements in smelting technologies have led to its widespread use as an intraosseous and periosteal implant in dentistry and orthopedics. Materials and Methods: Only case-control studies were used for the meta-analysis. Studies with a sample size of <5 were excluded. Cutaneous and epicutaneous tests were used in the study. Results: Three studies met the inclusion criteria. Titanium hypersensitivity is more prevalent in patients with titanium implants. Conclusions: It is also used in a variety of medical devices such as pacemakers and insulin pumps. Moreover, our external exposure to titanium is increasing. It is used in aerospace, chemical, and automobile industries. It is also used in jewelry, home furnishings, and in making sports and marine equipment. Titanium implants increase the possibility of developing titanium hypersensitivity, and thus, it should be considered as a major factor in unexplained implant failure where other causes have been excluded.